Oscillations et réaffirmations du genre dans les petites annonces de l’Intermédiaire Discret 1921-1939 - Claire-Lise Gaillard (Genre & Histoire)
The following article focuses on matrimonial matchmakers during the interwar period in France. It analyzes the more than 4000 classified advertisements placed in L’intermédiaire discret, a newspaper based in Bordeaux, between 1921 and 1940. Through these short texts, single men and women sketched the ideal roles which they ascribed to each sex through their descriptions of their ideal wife or husband. Classified advertisements this provide a unique window onto changes into the marital expectations of men and women during the interwar years in France. They provided a space in which traditional gender roles were powerfully reaffirmed by making explicit the rules of selection following the logic of a competitive market.